2021
DOI: 10.1111/aab.12689
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term fertilisation regimes influence the diversity and community of wheat leaf bacterial endophytes

Abstract: Plant endophytes exhibit an excellent ability to promote plant growth and control plant diseases. However, the influence of long‐term fertilisation regimes on the diversity and community of plant endophytes has seldom been reported. In this research, Illumina MiSeq sequencing was used to investigate the effect of 34 years of different fertilisation regimes on the diversity and community of wheat (Triticum aestivum L.) leaf endophytes. Results showed that different fertilisation regimes could significantly infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…3). According to research found that most microbial community have little difference at phylum level, which is basically consistent with the results of this study, which fully demonstrated the similarity of microbes in larger taxonomic units (Rim et al, 2021;Sun et al, 2021). At present, endophytes can be isolated from various parts and organs of studied plants, such as root, stem, leaf, fruit, and seed, and the structure composition and abundance of endophytes will change with different plant varieties, parts, and development periods (Dong et al, 2018;Lv et al, 2021).…”
Section: Microbial Diversity Analysissupporting
confidence: 91%
“…3). According to research found that most microbial community have little difference at phylum level, which is basically consistent with the results of this study, which fully demonstrated the similarity of microbes in larger taxonomic units (Rim et al, 2021;Sun et al, 2021). At present, endophytes can be isolated from various parts and organs of studied plants, such as root, stem, leaf, fruit, and seed, and the structure composition and abundance of endophytes will change with different plant varieties, parts, and development periods (Dong et al, 2018;Lv et al, 2021).…”
Section: Microbial Diversity Analysissupporting
confidence: 91%
“…All the constructed libraries were then sequenced on the Illumina Mi-Seq platform, this done by the Majorbio Co. Ltd. (Shanghai, Chia). The ensuing raw sequence data were filtered as previously described (Sun et al 2021 ). All the sequences data were uploaded in NCBI Sequence Read Archive database.…”
Section: Methodsmentioning
confidence: 99%
“…Further analysis showed that Proteobacteria, Pseudomonadaceae, Ascomycota, and Aspergillus were the dominant bacteria and fungi in the leaves of Idesia polycarpa, and these are similar to the endophytic bacteria found in other plants [30]. Previous studies have shown that microorganisms such as Proteobacteria, Pseudomonadaceae, and Aspergillus play an important role in enhancing plant resistance, promoting plant growth, and preventing disease [31]. According to Liu et al [32], phyllosphere bacteria differed at the genus level between male and female Fraxinus chinensis.…”
Section: Endophytes In Idesia Polycarpa Leavesmentioning
confidence: 57%